COVID-19, Vaccination, and Female Fertility in the Czech Republic - Kolatorova, Lucie; Adamcova, Karolina; Vitku, Jana; Horackova, Lenka; Simkova, Marketa; Hornova, Marketa; Vosatkova, Michala; Vaisova, Veronika; Parizek, Antonin; Duskova, Michaela (International journal of molecular sciences, 2022)
The fast-track process to approve vaccines against COVID-19 has raised questions about their safety, especially in relation to fertility. Over the last 2 years, studies have appeared monitoring female fertility, especially from assisted reproduction centers or in animal experiments. However, studies monitoring healthy populations are still limited. The aim of our study was to monitor the relevant parameters of female fertility (sex and other steroids, LH, FSH, SHBG, Antimüllerian hormone and antral follicle count) before and then 2-4 months after the third dose of vaccination against COVID-19 in a group of 25 healthy fertile woman. In addition, anti-SARS-CoV-2 and anti-SARS-CoV-2S antibodies were determined. We did not observe significant changes in the measured parameters before and after the third dose of vaccination. By comparing levels of the analytes with antibodies indicating a prior COVID-19 infection, we found that women who had experienced the disease had statistically lower levels of estrone, estradiol, SHBG and 5α-dihydroprogesterone, and conversely, higher levels of androgen active dehydroepiandrosterone and dihydrotestosterone. Our results confirm that vaccination does not affect female fertility, and that what fertile women should be worried about is not vaccination, but rather COVID-19 infection itself.
Keywords: COVID-19 Vaccines; estron; infection; antral follicle count; Androgens; vakcíny proti COVID-19; fertilita; Dehydroepiandrosterone; safety; androgeny; Česká republika; Anti-Mullerian Hormone; Dihydrotestosterone; COVID-19; antimülleriánský hormon; 20-alpha-Dihydroprogesterone; Czech Republic; ženské pohlaví; zvířata; Humans; Follicle Stimulating Hormone; Fertility; Estradiol; folikuly stimulující hormon; steroids; woman fertility; Estrone; dehydroepiandrosteron; dihydrotestosteron; 20-alfa-dihydroprogesteron; Female; estradiol; lidé; AMH; vaccination; Animals